P55 | ENDOTHELIAL THYMIDINE PHOSPHORYLASE DEFICIENCY TRIGGERS MORPHO-FUNCTIONAL DEGE-NERATION OF ENTERIC NEURONS AND REDUCES INTESTINAL STEM CELL PROLIFERATION (European Journal of Histochemistry)
The enteric nervous system (ENS) operates within a complex neurovascular niche where endothelial thymidine phosphorylase (TP) regulates vascular integrity. In mitochondrial neurogastrointestinal encephalomyopathy (MNGIE), TP is genetically absent, resulting in enteric neuronal loss and microvascular abnormalities1. Of note, MNGIE leads to a severe dysmotility disorder called chronic intestinal pseudo-obstruction (CIPO)2. Remarkably, in a cohort of idiopathic CIPO patients, we revealed through histochemical analysis a scenario similar to MINGIE, with a 50% reduction in jejunal TP correlating with vascular alterations and partial denervation. Moreover, we observed that TP downregulation leads to impaired angiogenesis. Under this light, we investigated whether endothelial TP deficiency directly affects enteric neurons and intestinal epithelial stem cells. Primary murine myenteric neurons and intestinal epithelial organoids (enteroids) were exposed to conditioned medium from 50% TP-silenced endothelial cells. Immunofluorescence and live imaging revealed neurite fragmentation and increased glial and fibroblast proliferation, while neuronal counts remained stable. Stress features included neuronal swelling and elevated nNOS expression. Electrophysiological analysis showed a 200% spike rate increase after acute exposure, followed by complete activity loss within 24h, with no recovery after acetylcholine stimulation. Interestingly, in enteroids, Ki-67 expression decreased by 47%, indicating impaired epithelial proliferation. These results demonstrate that TP deficiency in endothelial cells alters both ENS and epithelial compartment integrity, suggesting TP as a histochemically traceable factor crucial for gut neuroepithelial homeostasis. Finally, this work supports the hypothesis of a vascular-driven mechanism contributing to neuronal and stem cell dysfunction in both idiopathic and genetic forms of CIPO.